Long-Term Prognostic Value of Restitution Slope in Patients with Ischemic and Dilated Cardiomyopathies - Dorenkamp, Marc (Public Library of Science, 2013)
BACKGROUND: An action potential duration (APD) restitution curve with a steep slope ≥1 has been associated with increased susceptibility for malignant ventricular arrhythmias. We aimed to evaluate the “restitution hypothesis” and tested ventricular APD restitution slope as well as effective refractory period (ERP)/APD ratio for long-term prognostic value in patients with ischemic (ICM) or dilated cardiomyopathy (DCM). METHODOLOGY/PRINCIPAL FINDINGS: Monophasic action potentials were recorded in patients with ICM (n = 32) and DCM (n = 42) undergoing routine programmed ventricular stimulation (PVS). Left ventricular ejection fraction was 32±7% and 28±9%, respectively. APD and ERP were measured at baseline stimulation (S(1)) and upon introduction of one to three extrastimuli (S(2)–S(4)). ERP/APD ratios and the APD restitution curve were calculated and the maximum restitution slope was determined. After a mean follow-up of 6.1±3.0 years, the combined end-point of mortality and and/or implantable cardioverter-defibrillator shock was not predicted by restitution slope or ERP/APD ratios. Comparing S(2) vs. S(3) vs. S(4) extrastimuli for restitution slope (1.5±0.6 vs. 1.4±0.4 vs. 1.3±0.5; p = NS), additional extrastimuli did not lead to a steepening restitution slope. ERP/APD ratio decreased with additional extrastimuli (0.98±0.09 [S(1)] vs. 0.97±0.10 [S(2)] vs. 0.93±0.11 [S(3)]; p = 0.03 S(1) vs. S(3)). Positive PVS was strongly predictive of outcome (p = 0.006). CONCLUSIONS/SIGNIFICANCE: Neither ventricular APD restitution slope nor ERP/APD ratios predict outcome in patients with ICM or DCM.